Genes in treatment: Polygenic risk scores for different psychopathologies, neuroticism, educational attainment and IQ and the outcome of two different exposure-based fear treatments. (21st October 2021) - Wannemüller, André; Kumsta, Robert; Jöhren, Hans-Peter; Eley, Thalia C.; Teismann, Tobias; Moser, Dirk; Rayner, Christopher; Breen, Gerome; Coleman, Jonathan; Schaumburg, Svenja; Blackwell, Simon E.; Margraf, Jürgen
Abstract: Objectives: Evidence for a genetic influence on psychological treatment outcome so far has been inconsistent, likely due to the focus on candidate genes and the heterogeneity of the disorders treated. Using polygenic risk scores (PRS) in homogenous patient samples may increase the chance of detecting genetic influences. Methods: A sample of 342 phobic patients treated either for clinically relevant dental fear ( n = 189) or other (mixed) phobic fears ( n = 153) underwent highly standardised exposure-based CBT. A brief five-session format was used to treat dental fear, whereas longer multi-session treatments were used with the mixed-fear cohort. PRS were calculated based on large genetic studies of Neuroticism, Educational Attainment (EA), Intelligence, and four psychopathology domains. We compared PRS of post-treatment and follow-up remitters and non-remitters and regressed PRS on fear reduction percentages. Results: In the dental fear cohort, EA PRS were associated with treatment outcomes, i.e. drop-out, short- and long-term remission state, fear reduction, and attendance of subsequent dental appointments. In the mixed fear treatment cohort, no gene effects were observable. Conclusions: Results indicate the importance of EA-related traits for outcomes following brief, but not long, standardised exposure-based CBT. Such use of PRS may help inform selection and tailoring of treatments.